Analysis of Signal Attenuation in the Indosat Fiber to the Home (FTTH) Network at Three Fat Points and the Role of Closures in Optimizing Optical Signals in Cluster RW07, Dusun I, Madegondo, Sukoharjo Regency, Central Java - Mitahul Rizka; Aprinal Adila Asril; Popy Maria (Politeknik Negeri Padang, 2025)
The implementation of Fiber to the Home (FTTH) networks is an effective solution for providing high-quality telecommunication services with stable data speeds. This study was conducted on the FTTH network in Cluster RW 07, Dusun 1, Madegondo, Sukoharjo Regency, Central Java, to evaluate its feasibility based on PT. iForte's standards. These standards specify a receiving power range of -10 dBm to -21 dBm and a total attenuation range of 15 dB to 26 dB. The research process involved observation, optical power data collection, data processing, and analysis using the Power Link Budget parameter. The measurement results showed an improvement in network quality after optimization. The uplink and downlink attenuation at FAT 1, 6, and 11 experienced significant reductions, with the final attenuation values falling within the specified standard limits. For instance, at FAT 11, the downlink attenuation decreased by 1.10 dBm, representing one of the most significant improvements. These findings demonstrate that the FTTH network in the study area meets the feasibility criteria and delivers performance suitable for supporting user needs.